Self-Declare Halal Product Assurance System in Indonesia in The Review of Management Functions - Muhammad Aziz; Sholikah Sholikah; Nur Mazidah; Siti Marpuah; Thoriq Mutaali Albar (Journal of Halal Research, Policy, and Industry, 2025)
This study discusses the criteria for the halal product assurance system (SJPH) with a self-declaration mechanism in Indonesia from the perspective of George R. Terry's classical management functions. The background of the study is based on the importance of halal certification for micro and small enterprises (MSEs), as well as the existence of a self-declaration policy that allows business actors to declare the halal status of their products themselves. The purpose of the study is to analyze the criteria for the self-declaration SJPH based on BPJPH regulation Number 57/2023 using a management function framework (planning, organizing, directing, and controlling). This study uses a qualitative method with a library approach, through the study of national and international academic documents and literature related to halal certification and management theory. The results show that the self-declaration SJPH criteria include halal policies, a halal management team, raw material control, production procedures, training, internal audits, and reporting. From a management function perspective, these criteria are aligned with the principles of strategic planning, organizing resources, directing the workforce, and continuous quality control. The main implementation challenges are limited human resources, digital literacy, and financial capacity of MSEs, although opportunities for strengthening exist through institutional mentoring and market incentives. The theoretical contribution of this research is the expansion of management functions with a multi-actor coordination dimension, while its practical contribution is a roadmap for improving halal governance of MSEs in Indonesia.